Flintknive fra yngre bronzealder - Jensen, Helle Juel (Kuml, 2006)
Flint knives from Late Bronze Age Most flint tools from the Late Bronze Age are characterized by fortuitousness and technological opportunism, and very few can be grouped in stereotype forms as the ones known from earlier prehistoric periods. However, a single artefact group differs: the large, retouched blade knives sometimes also referred to as sickles or leaf-knifes. These knives represent a type characteristic of Denmark and Southern Sweden. Chronologically, they seem to belong to period V-VI of the Late Bronze Age. In the literature, reference has been made to these knives since the late 19th century, and especially the hafted specimen from Stenild Bog has attracted attention. Retouched blade knives are typically made from large, coarse flakes with a triangular or trapezoid cross section. One of the lateral edges normally has a complete or partial steep edge retouch, but the back may also consist of cortex or a combination of cortex and retouch. Several knives also have retouch for hafting along the base of the cutting edge. Using the material from the Bronze Age settlement Fosie IV as the base, N. Björnhem and U. Sävestad have divided the Swedish knives into two types, dependant on whether the distal end ends in an asymmetrical point (Type I), or in a fracture, or in a straight or convex truncation (Type II). This division seems to apply largely to the Danish material, although the latter displays a larger variation as regards manufacture quality and dimensions. Throughout the times, several researchers have been occupied with the function of the knives, and - although the variation as to the use of the tools is certainly not yet uncovered - we do have sporadic insight, especially thanks to use-wear analyses using the ‘High Power’ method (HPA). However, this method implies that the surface of the flint tool is fairly well preserved, and unfortunately, the surfaces of the majority of the knives analysed so far are partly or completely deteriorated, so that only the most vigorous use polish has survived. Consequently, our knowledge of use and hafting primarily comprises tools that have been in contact with siliceous plant material such as cereals and reeds, and which have therefore obtained a strong lacquer-like shine or gloss. Already in 1898, Chr. Blinkenberg decided that the hafted Stenild knife was a sickle due to the heavy gloss along the cutting edge. Since then, it has been generally accepted that at least glossed specimens of the knives were used as sickles. Most recently, the HPA method has rectified this interpretation, as there are subtle, yet very real differences between polishing caused by cereal cutting and the cutting of even more siliceous plant materials such as – typically – reeds. Both functions are represented on the edges of Bronze Age knives: The Stenild sickle should still be considered a regular harvesting tool, whereas others seem to have been used for cutting reeds. As mentioned, the function of a large group of knives cannot be determined due to transformation of their surface. However, flaking along the edge of the knives indicates that they were used for hard material such as wood, and so a function as leaf-knife – as the tools are often called in the literature – cannot be ruled out. Preliminary use-wear analyses of large blade knives from North and Northwest Jutland have further shown that a number of these were hafted the same way as the Stenild sickle, i.e. perpendicular to the haft. Whether this hafting method is regional, and whether the method only comprises knives for plant cutting (which are so far the only that can be analysed), cannot yet be determined. The blade knives appear primarily in the settlements from the Late Bronze Age. To this must be added a special group of finds, which may best be described as workshop localities or production sites. The fact that attention has been focused on this category is mainly a result of analytical work made by Swedish archaeologists. Björnhem and Säfvestad thus called attention to the fact that the Fosie IV settlement did not contain waste from knife production and suggested that this must have taken place elsewhere. Furthermore, based on replicative and technological studies, A. Högberg argued that the knives must be characterised as a much-standardised product, which was also extremely demanding in raw materials and so must have been produced in areas rich of flint. Although only few technological analyses of the Danish Bronze Age flint have been made so far, the presence of localities with many knives and preforms of these in the form of heavy blanks indicate that the same production conditions apply to large parts of the Danish material. A third and last context in which the flint knives occur are the so-called deposits or assemblages known from Denmark and Southern Sweden. Most of these finds were made in the late 19th/early 20th century, and only rarely by professionals. Observations and documentation of the find conditions are therefore limited. The deposits were typically found in wetlands, during peat digging or ploughing in previous bogs, or on a flat field, sometimes underneath or near a large stone. A few of the deposits were found in connection with settlements. Best illustrated is the Danish find from House XII in the settlement Spjald in Northwest Jutland. The artefacts that had been placed in a posthole consisted of six heavy blade knives, a large scraper, the bottom of an earthenware vessel, and a mass of resin. Apart from the Stenild sickle, all registered deposits are composed of several knives and often also of preforms. According to M.Wyszomirski and K.Ebbesen, who published surveys of the Swedish and the Danish finds respectively, the majority of these comprise between two and ten items, at rare intervals more. The many deposits of metal objects during the Bronze Age are for the majority interpreted as material left behind from more or less complex religious or political manifestations. The question now is how the deposits of large blade knives should be interpreted in this connection. Over the time, several researchers have called attention to the fact that the location of the finds coincides with the supposed sacrifices of metals. Researchers such as Müller, Blinkenberg, and most recently Ebbesen therefore have no doubt as to the ritual character of the finds: the apparent technological worthlessness of the knives and the fact that they were all used indicate that they represent a ‘popular’ communication with the supernatural, attached to basic activities and to man’s seasonal exploitation of nature. An important factor in the quoted argumentation is the repeated understanding of the expedient nature of the knives, or their technological ‘worthlessness’. However, a lot seems to indicate that these knives and their origin have been underestimated, and in this connection, it is relevant to return to the Swedish technological investigations and the existence of so-called workshop sites. As accentuated by especially Högberg, the blade knives were apparently specialised tools demanding considerable resources, made elsewhere and from there distributed for use in the settlements. Although the Danish find picture is not quite as categorical as the Swedish one, at least some of the knives here follow the same pattern, including the knives from the deposits – all large, between 100 and 150 mm long. We can thus establish that the knives were not an expression of random bungling, but that at least groups of these were specially made and part of a distribution pattern, the extent and organisation of which is vague for the time being. To sum up we may therefore conclude that the deposited knives were hardly as technologically and materially worthless as they have been typically considered. However, a re-evaluation of the knives does not necessarily impair the prevalent sacrificial find interpretation, as »value« is often an important aspect in connection with sacrifices. Another and more weighty argument in favour of sacrifice is the circumstance that the knives were used and may therefore obviously be seen as representatives of finished activities of some importance to the individuals responsible for the deposits. An insight into the function of the knives through a use-wear analysis will obviously be an important key to clarifying this question. As mentioned, the preservation state of the hitherto analysed knives has been a bit of an obstacle. However, the investigation of another number of finds still remains. Helle Juel Jensen Afdeling for Forhistorisk Arkæologi Institut for Antropologi, Arkæologi og Lingvistik Aarhus Universitet Translated by Annette Lerche Trolle